Coefficient Estimates for Bi-univalent Functions Defined by (P, Q) Analogue of the Salagean Differential Operator Related to the Chebyshev Polynomials - Trailokya Panigrahi; Susanta Kumar Mohapatra (Journal of Mathematical and Fundamental Sciences, 2021)
In the present investigation we use the Jackson (p,q)-differential operator to introduce the extended Salagean operator denoted by Rkp,q. Certain bi-univalent function classes based on operator Rkp,q related to the Chebyshev polynomials are introduced. First, two coefficient bounds and Fekete-Szego inequalities for the function classes are established. A number of corollaries are developed by varying parameters involved.